Socio-Economic Impact of Subsidy Removal on Academic Staff, Students, And University Administration in Nigeria - Hassan , Imam I. (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
This study was carried out on the socio-economic impact of subsidy removal on academic staff, students, and university administration in Nigeria. Secondary data were used in the paper. The data were collected from print and online publications. The study established that subsidy removal in Nigeria has a sociological impact on academic staff, students, and university administration. The study specifically identified increment in school fees and social vices like prostitution, kidnapping, robbery, and academic corruption as the social impacts of subsidy removal on academic staff, students, and university administration in Nigeria. Based on this finding, the study recommended that federal and state governments implement all palliative measures outlined to reduce the impact of subsidy removal, and the Government should increase the funding of universities to enable administrators to administer the universities well. Scholarships should be granted to tertiary institution students, and academic staff salaries should be increased.